Palladium electrodeposited on silver alloy as electrocatalyst for hydrogen production via water electrolysis - Custodio, Aisa Grace D. (College of Engineering, University of the Philippines Diliman, 2014)
Effective and less expensive electrocatalyst is needed for higher efficiency of water electrolysis to produce hydrogen. Electrocatalysis decreases the overpotential, thus reducing energy needed for electrolysis. This theses presents Palladium (Pd) electroplated on a silver (Ag) substrate as a potential alternative electrocatalyst to Platinum (Pt). Palladium, a metal that belongs to the noble group of metals has the unusual ability to absorb hydrogen. To reduce the usage of bulk palladium in this study, Pd electrodeposition is used to deposit Pd on smooth and rough Ag alloy as substrates. Effects of plating voltage (current density) and deposition time on the amount and quality of Pd deposit will be investigated. Surface morphology and compositional characteristics of the electrodes will be observed using Scanning Electron Microscopy (SEM), Optical Microscopy, and X-ray Fluorescence Analysis (XRF). The effect of heat treatment (annealing), surface roughness and the type of electrolyte solution on electrocatalytic activity of the electrocatalyst is determined using measurements from linear sweep volatammetry (LSV) and cyclic voltammetry (CV). The average onsets of HER and OER of Pd electrodes at acid electrolyte are -0.25V and 1.4V, respectively while Pt is -0.23V and 1.5V. At basic electrolyte, average onsets of HER and OER of Pd electrodes are -1V and 0.67V, respectively while Pt is -1V and 0.7V. Thus, Pd electrodes have comparable electrocatalytic properties to Pt as cathode in both acidic and basic electrolyte. It can also be used as anode in basic media. On the other hand, Pd on Ag alloy electrode may fail as anode in acidic water electrolysis due to removal of Pd during stability test. Two-way ANOVA showed that surface roughness and type of electrolyte significanlty affect the electrocatalytical activity of Pd in the hydrogen evolution region while only the type of electrolyte has significant effect in the oxygen evolution region.